Ontological Support for Harmonization and Integration of Ukrzaliznytsia Information Systems Data - Zhuchyi, L. I (Science and Transport Progress, 2022)
Purpose. The development strategy of Ukrzaliznytsia includes the following areas: integration and standardization of information systems, increasing the truthfulness of data and automating business processes. The integration of railway information systems is possible by ontological means without changing their structure. In this work, the main aim is the analysis of existing transportation ontological developments and determination of approaches to the application of related domains developments to the objectives of Ukrzaliznytsia’s development. Methodology. Ontological developments are systematized according to the type and format of their resources, the level of data integration, and the goals of ontology-based software. Methods of system analysis are used. Findings. The analysis showed that European Union railway transport ontologies are used to integrate infrastructure description data, train timetables, and others. At the same time, insufficient attention is paid to the regulatory support of the transportation process. There are software tools for annotating texts, extracting knowledge from tables and developing ontologies, but they are not used to support the Ukrainian railway transportation process. It has been determined that the actual problem is normative documentation annotation to establish a link between the ontology and the regulation texts. Originality. The basis for achieving the development goals of Ukrzaliznytsia by ontological means was laid, using the analysis and systematization of existing ontological developments of transport and related domains. The possibilities of using ontological means in railway transport are scientifically substantiated for: formalization of regulatory support; data transformations; data integration; checking the consistency of information systems data and regulations. Practical value. The work made it possible to identify the most significant ontological projects in transport. The foundations for the implementation of the conceptualization of the tabular representation of knowledge and the development of an ontology for the integration of models of railway subsystems have been laid.